RANCANG BANGUN MESIN PEMISAH DAGING KELAPA DARI TEMPURUNG - Ahmad Supriyadi (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Coconut’s endosperm separation process has been done manually in the home industry the process is that coconut fiber separation process by using short sword kind of crowbar, and coconut shell separation process by using short sword . All of process uses human’s hand ( manual ). By the process, it will containt high accident risk it also needs long time and needs a lot of workers. A worker can reach 30 coconuts/hour in capacity only and there are part of coconut shell stick on coconut’s endosperm although in minimum size. For separation process eficiency rises, needs mechanical separation process. Those by design and build “ Endosperm separating machine “, which can produce clean and fullfill the home industry standart which has small fund. Design and build process starts by knowing force need for slice the coconut and force need for separating endosperm process by shape testing, slicer dimensions and separotor dimensions, machine mechanism, kind of motor, and power to run the process.Endosperm separating machine completed by slicer and motored by electrical motor ½ HP, 1450 rpm by three steps transmition consist of belt, pulley for slicing process and gear box 1 : 40, bevel gear, for separation process. Capacity by using this machine, production capacity can reach 90 coconuts/hour with separation quality is better than manual process. Keywords : coconut, coconut shell, separation, crowbar